The Impact of Subchronic Soybean Milk and Genistein Supplementation on Pancreatic Fatty Infiltrations of Sprague Dawley Male Mice - Sasiarini, Laksmi; Soeatmadji, Djoko Wahono; Santoso, Aktaruddin Arief (Universitas Brawijaya, 2020)
Isoflavones (genistein, daidzein) on soybean milk have phytoestrogenic properties. In Asia, the blood phytoestrogen levels can reach 160 ng/ml (80 times higher than Western). This may potentially disrupt endocrine functions regarding its binding with estrogen receptors.. Since the function and distribution of adipose tissues are regulated by estrogen receptors, the reduction of estrogen receptor-Î±(ERÎ±) results in ectopic fats distribution around visceral tissues, such as the pancreas. Aim: To investigate the impact of subchronic soybean milk and genistein supplementation on pancreatic fatty infiltrations in mice. Methods: The experiment used 35 Sprague dawley male mice under 7 treatment groups within 60 days: negative control with standard rationed food, 3 groups with a variable dose of soybean milk: 100 mg, 200 mg, and 400 mg, and 3 groups with a variable dose of genistein: 0.4 mg, 0.8 mg, and 1.6 mg. Histological measurements on the level of pancreatic fatty infiltrations were conducted after. Analyses used Kruskal-Wallis and post-hoc Mann-Whitney. Results: Medium to a high level of pancreatic fatty infiltrations were found at the control group while there is a decreasing trend on the level of pancreatic fatty infiltrations on groups with soybean milk and subchronic genistein compared with the control group, proportional to higher dosage supplementation. The reduction of pancreatic fatty infiltration levels on groups with soybean milk and subchronic genistein supplementation is not statistically significant compared to control. Conclusion: Â Supplementation of soybean milk and subchronic genistein do not significantly reduce the levels of pancreatic fatty infiltrations in Sprague dawley male mice.